Expansion of gelatinous macrozooplankton in the open Black Sea off Crimea under the weather events of recent years - ANNINSKY, BORYS E.; FINENKO, GALINA A.; DATSYK, NATALYA A.; HUBAREVA, ELENA S. (Mediterranean Marine Science, 2022)
Species composition, abundance, and distribution of gelatinous macroplankton in coastal and deep-sea areas of the Black Sea in November 2017 are discussed. Despite the fact that the species composition of gelatinous macroplankton (medusa Aurelia aurita, ctenophores Mnemiopsis leidyi, Pleurobrachia pileus, and Beroe ovata) in 2017 did not differ from that in 2016, structural changes occurred. In autumn 2017 A. aurita and B. ovata biomass was higher than in 2016 whereas the inverse difference was observed in their abundance values. Namely, A. aurita biomass was on average 514 g m-2 and 634 g m-2 in the outer shelf and deep-sea areas, respectively. Both parameters of M. leidyi and P. pileus declined in 2017 compared to the previous year. In addition, the share of large-sized individuals increased in 2017, while that of small-sized animals decreased, in comparison with 2016. The number of small individuals increased in P. pileus and decreased in M. leidyi, although their biomass before the seasonal appearance of B. ovata in plankton was close to that in 2016. The unprecedented increase in the medusae biomass in November 2017 could not be explained only by the competition with planktivorous ctenophores and may indicate alternative drivers controlling the population dynamics of A. aurita in the Black Sea. A negative correlation was depicted between the Danube discharge in February-March and the rate of somatic growth of A. aurita.